PENGARUH BEBAN KERJA, KONFLIK KERJA, DAN KOMPENSASI TERHADAP KOMITMEN KERJA PADA GURU - Septyanti, Ratih (Universitas Bina Taruna Gorontalo, 2025)
Human Resource Management is a part of management that focuses on establishing the quality of the workforce. Therefore, it is very important to pay attention to human resources in a company or agency, including looking at workload, work conflict, and compensation in order to create comfort for the workforce to achieve high work commitment. This research aims to see how much influence workload, work conflict, and compensation have on work commitment of Maitreyawira School teachers in Palembang. This research uses quantitative research with data collection techniques using questionnaires. The data obtained was processed using Smart PLS 3.2.9. Workload indicators are working conditions, working time, and work targets, while work conflict indicators are differences, dependency, friction, and communication styles. The compensation indicators are direct financial compensation, indirect financial compensation, non-financial compensation related to work, and non-financial compensation related to the environment. The work commitment variable itself has indicators of affective commitment, continuous commitment and normative commitment. The research results show that workload has a negative and significant effect, work conflict has a negative and significant effect, and compensation has a positive and significant effect.